South African Regulatory Authority: The Impact of Reliance on the Review Process Leading to Improved Patient Access - Keyter, Andrea; Salek, Sam; Danks, Lorraine; Nkambule, Portia; Semete-Makokotlela, Boitumelo; Walker, Stuart (Frontiers in Pharmacology, 2021)
Background: The aims of this study were to compare the overall regulatory review timelines achieved by the South African Health Products Regulatory Authority (SAHPRA) in 2020 to the timelines historically achieved by the Medicines Control Council (MCC). This study also aimed to evaluate the regulatory review processes and the good review practices that have been implemented by SAHPRA to support the assessment of new chemical entities and generic product applications for market authorization in the business-as-usual and backlog process streams. Methods: A questionnaire was completed and verified by SAHPRA to describe the structure of the organization, the resources available, the process for regulatory review of new chemical entities and generic products and the level of implementation of good review practices and regulatory decision-making practices for market authorization. Data were collected and analyzed on the overall approval timelines for new chemical entities and generic products registered by SAHPRA in 2020 in the business-as-usual and backlog process streams. Results: A full, independent scientific review was conducted for all new chemical entities and generic product applications in the business-as-usual stream. Facilitated regulatory pathways were introduced for the review of new chemical entities and generic products in the backlog stream. As a result, the timelines for approval of applications in the backlog stream were 68% quicker for both new chemical entities and generics, using facilitated regulatory pathways, such as abridged and verification review models. Conclusion: The comparisons made through this study provided insight into the improvements that have been made through the establishment of SAHPRA and the transition in 2018 from the MCC. The re-engineered processes that have been developed and implemented by SAHPRA to address the backlog in the review of the applications for market authorization have demonstrated a decrease in the overall median approval times. The expansion of these processes into the routine review of medical products will contribute to the enhanced regulatory performance of SAHPRA and patients’ access to new medicines.